2018
DOI: 10.1002/lom3.10264
|View full text |Cite
|
Sign up to set email alerts
|

Influence of commercial DNA extraction kit choice on prokaryotic community metrics in marine sediment

Abstract: Commercial DNA extraction kits are widely used for cultivation-free surveys of marine sediment. However, the consequences of popular extraction-kit choices for sequence-based biological inferences about marine sedimentary communities have not previously been exhaustively assessed. To address this issue, we extracted DNA from multiple paired subsamples of marine sediment using two popular commercial extraction kits (MO BIO Laboratories PowerSoil V R DNA isolation kit and MP Biomedicals FastDNA TM Spin Kit for S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 50 publications
4
12
0
Order By: Relevance
“…We could not demonstrate a significant effect of extraction kit on overall alpha diversity, and studies showing no effect or significant effect of DNA extraction kit on microbial alpha diversity are available in the literature (Fiedorova et al, 2019;Hallmaier-Wacker, Lueert, Roos, & Knauf, 2018;Mattei et al, 2019;Ramírez, Graham, & D'Hondt, 2018). Nevertheless, we observed that the tested extraction kits differentially detected less abundant taxa, a finding corroborated in previous DNA extraction kits comparisons (Liu, Xue, & Yang, 2019).…”
Section: Discussionsupporting
confidence: 80%
“…We could not demonstrate a significant effect of extraction kit on overall alpha diversity, and studies showing no effect or significant effect of DNA extraction kit on microbial alpha diversity are available in the literature (Fiedorova et al, 2019;Hallmaier-Wacker, Lueert, Roos, & Knauf, 2018;Mattei et al, 2019;Ramírez, Graham, & D'Hondt, 2018). Nevertheless, we observed that the tested extraction kits differentially detected less abundant taxa, a finding corroborated in previous DNA extraction kits comparisons (Liu, Xue, & Yang, 2019).…”
Section: Discussionsupporting
confidence: 80%
“…This suggests that there are likely to be taxon-specific variations in cell lysis between the kits, especially in the eukaryotic dataset. This finding is in agreement with other studies that have found a similar trend ( Carrigg et al, 2007 ; Lekang, Thompson & Troedsson, 2015 ; Ramírez, Graham & D’Hondt, 2018 ). This could be further tested by using positive extraction controls such as a known mock prokaryotic community, allowing for the assessment of lysis efficiencies amongst kits ( Hermans, Buckley & Lear, 2018 ).…”
Section: Discussionsupporting
confidence: 94%
“…This approach covered the available thermal range of cored sediment, while providing sufficient material for coordinated experiments with other cruise participants, and accommodating temperature fluctuations due to pulsating hydrothermal flows that impact surficial (5 to 10 cmbsf) sediments [ 14 ]. Total DNA was extracted using the FastDNA TM Spin Kit for Soil (MP Biomedicals), as recommended for marine sediment [ 35 ], following the manufacturer’s protocol. Bacterial and archaeal SSU rRNA hypervariable region 4–5 (V4-V5) amplicons were generated using the 515F-Y ( ) and 926R ( ) primers and customized thermocycling parameters [ 36 ].…”
Section: Methodsmentioning
confidence: 99%